A multi-band dual-layer encoded microwave absorber with angle selectivity - Senfeng Lai; Jingyi Luo; Junxian Tan; Huiyuan Fu (Materials & Design)
This work aims to develop a microwave absorber with tunable angles, utilizing 1-bit coding to achieve precise regulation of absorption angles across different coding states, resulting in selective absorption exceeding 99 %. To meet the pressing demands of modern wireless communication systems for controllable, angle-selective, transparent, and multi-band microwave absorbers, the designed absorber consists of upper and lower transparent coded structures with an intermediate air layer.Further analysis of the absorber’s operating principle revealed that under normal incidence conditions, the absorber exhibits four resonant peaks at 13.1 GHz, 25.0 GHz, 33.5 GHz, and 35.6 GHz, with absorption rates exceeding 99.8 %.Ultimately, we fabricated samples and measured their absorption performance within the frequency range of 0–26 GHz under experimental conditions. The experimental results showed that the absorber demonstrated selective absorption exceeding 90 % for various angles of incidence and frequencies; specifically, it achieved over 99 % absorption only at 2 GHz at an oblique incidence angle of 60°, and over 90 % absorption only at 18 GHz at an incidence angle of 30°.This microwave absorber, capable of achieving 99 % absorption at specific angles and frequencies, showcases significant value in multiple areas such as electromagnetic compatibility, signal integrity, military applications, and communication fields.